3D margin assessment predicts local tumor progression after ablation of colorectal cancer liver metastases. (31st December 2022) - Vasiniotis Kamarinos, Nikiforos; Gonen, Mithat; Sotirchos, Vlasios; Kaye, Elena; Petre, Elena N.; Solomon, Stephen B.; Erinjeri, Joseph P.; Ziv, Etay; Kirov, Assen; Sofocleous, Constantinos T.
Abstract: Objective: To determine the feasibility and prognostic value of 3D measuring of the ablation margins using a dedicated image registration software. Methods: This retrospective study included 104 colorectal liver metastases in 68 consecutive patients that underwent microwave ablation between 08/2012 and 08/2019. The minimal ablation margin (MM) was measured in 2D using anatomic landmarks on contrast enhanced CT(CECT) 4–8 weeks post-ablation, and in 3D using an image registration software and immediate post-ablation CECT. Local tumor progression (LTP) was assessed by imaging up to 24 months after ablation. A blinded interventional radiologist provided feedback on the possibility of additional ablation after examining the 3D-margin measurements. Results: The 3D-margin assessment was completed in 79/104 (76%) tumors without the need for target manipulation. In 25/104 (24%) tumors, manipulation was required due to image misregistration. LTP was observed in 40/104 (38.5%) tumors: 92.5% vs 7.5% for those with margin <5mm vs ≥5mm, respectively ( p  = 0.0001). The 2D and 3D-assessments identified margin <5mm in 17/104 (16%), and in 74/104 (71%) ablated tumors, respectively ( p  < 0.01). The sensitivity and specificity of the 3D software for predicting LTP was 93% (37/40) and 42% (27/64), respectively. Additional ablation to achieve a MM of 5 mm would have been offered in 26/37 cases if the 3D-margin assessment was available intraoperatively. Conclusion: Image registration software can measure ablation margins and detect MM under 5 mm intraoperatively, with significantly higher sensitivity than the 2D technique using landmarks on the post-ablation CECT. The identification of a margin under 5 mm is strongly associated with LTP.